Diagnostic Value of Spectral-Domain Optical Coherence Tomography for Polypoidal Choroidal Vasculopathy: A Systematic Review and Meta-Analysis - Jiang, Yang; Qi, Shixin (Frontiers in Medicine, 2022)
Purpose To evaluate the diagnostic value of spectral-domain optical coherence tomography (SD-OCT) for polypoidal choroidal vasculopathy (PCV). Methods A search of electronic databases was conducted from 2010 to 2021 to review the relevant literature on SD-OCT to identify PCV and other lesions causing serious or serosanguinous retinal pigment epithelial detachment (PED), specifically neovascular age-related macular degeneration (nvAMD). The QUADAS-2 scale was used to evaluate the quality of the literature. We performed a meta-analysis, including heterogeneity tests, analyze and synthesize the study data, meta-regression analysis, subgroup analysis, Fagan's plot, sensitivity analysis and publication bias tests. Results A total of 12 related studies involving 1,348 eyes were included in this study, and the random-effects model was used for meta-analysis. The results showed that the pooled sensitivity of SD-OCT in the diagnosis of PCV was 0.87 (95% CI: 0.84–0.89), the pooled specificity was 0.83 (95% CI: 0.80–0.86), and the pooled positive/negative likelihood ratios were 5.38 (95% CI: 3.28–8.80) and 0.16 (95% CI: 0.10–0.25), respectively. The diagnostic odds ratio (DOR) was 36.07 (95% CI: 15.98–81.40), and the area under the sROC curve (AUC) was 0.9429. When the pre–test probability was set at 20%, the post-test positive and negative probabilities were 58% and 4%, respectively. Meta-regression indicated that race was the primary source of heterogeneity (P <0.05). The Deeks' funnel plot showed no significant publication bias in this study (P>0.05). Conclusion SD-OCT has high sensitivity and specificity for the diagnosis of PCV, as well as significant clinical applicability. Since color fundus photography (CFP) is more clinically available and can improve the diagnostic efficacy, we recommend SD-OCT combined with CFP to diagnose PCV, especially without indocyanine green angiography (ICGA). Systematic Review Registration https://inplasy.com/inplasy-2021-12-0048/, identifier: INPLASY2021120048.